Newly developed controlled release subcutaneous formulation for tramadol hydrochloride - Mostafa Mabrouk; Hanan H. Beherei; Shaimaa ElShebiney; Masaru Tanaka (Elsevier, 2018)
This study presents a drug delivery system of poly (Ɛ-caprolactone) (PCL) ribbons to optimize the pharmaceutical action of tramadol for the first time according to our knowledge. PCL ribbons were fabricated and loaded with tramadol HCl. Ribbons were prepared by slip casting technique and coated with dipping technique with β-cyclodextrin. The chemical integrity and surface morphology of the ribbons were confirmed using FTIR and SEM coupled with EDX. In addition, thermodynamic behavior of the fabricated ribbons was investigated using DSC/TGA. Tramadol loading into PCL ribbons, biodegradation of ribbons and tramadol release kinetics were studied in PBS.The results revealed that the formulated composition did not affect the chemical integrity of the drug. Furthermore, SEM/EDX confirmed the inclusion of tramadol into the PCL matrix in homogenous distribution pattern without any observation of porous structure. The particle size of loaded tramadol was found to be in the range of (2-4 nm). The formulated composition did not affect the chemical integrity of the drug and should be further investigated for bioavailability. Tramadol exhibited controlled release behavior from PCL ribbons up to 45 days governed mainly by diffusion mechanism. The fabricated ribbons have a great potentiality to be implemented in the long term subcutaneous delivery of tramadol. Keywords: Tramadol, Polycaprolcatone, Subcutaneous membrane, Ribbons, β-Cyclodextrin, Controlled release